Professional competencies and their relationship to the psychosocial adjustment of physical education teachers from the point of view of middle school principals in the Salah al-Din Education Directorate" (Journal of the College of Basic Education, 2024)
The world is witnessing a widespread trend towards taking care of middle school students because it is considered an important stage of human awareness, especially in the field of physical education, and is supported by developments taking place in societies, including professional competencies, psychosocial compatibility, and other qualities. This comprehensive development is achieved by education by building the individual in an integrated manner. Every aspect has its importance and place in this world, and without it, the individual’s personality is not complete. Physical education is a type of education and is a way to hone a person in developing his sportsmanship.The researcher chose the research population of physical education teachers from the point of view of middle school principals in the Salah al-Din Education Directorate, and their number was (185). After the study samples were determined, the researcher proceeded to prepare and build the standards for his study and prepare the questionnaire forms for each standard, and the necessary procedures were taken. To prepare and build standards, information was collected from the questionnaires distributed to the research samples. The researcher used the statistical package (SPSS) to extract the research results, then tabulate the obtained data into tables, process it, display and analyze the results, and then discuss them.The researcher reached a number of conclusions, the most important of which are:The presence of professional competencies for physical education teachers in the Tarbiat Salah Directorate.Achieving educational goals that would increase the professional competencies of physical education teachersIn light of this, the researcher recommended:Conduct a study that addresses economic aspects and their impact on professional competencies and psychosocial adjustment.Benefiting from the list of professional competencies and psychosocial compatibility by those concerned in the performance and evaluation of physical education teachers